THE INFLUENCE OF THE TAGLINE “FREE SHIPPING”, FLASH SALE AND SOCIO-ECONOMIC STATUS OF PARENTS ON CONSUMPTIVE BEHAVIOR IN SHOPEE E-COMMERCE ON SHARIA ECONOMICS STUDENTS IN PALEMBANG CITY UNIVERSITIES THROUGH HEDONIC SHOPPING MOTIVATION AS AN INTERVENING VARIABLE - Iffatur Rohmah; Rina Antasari; Deky Anwar (CV. Cendikiawan Muda Sriwijaya, 2025)
This study aims to analyze the influence of the